Process-Oriented Tolerance and Variation Management: Review and Classification - Litzenburger, Philipp; Götz, Stefan; Margies, Lennard; Bode, Christoph; Müller, Rainer; Wartzack, Sandro (Applied Sciences, 2024)
In the context of tolerance management, the consideration of manufacturing and assembly processes is becoming increasingly important. The main drivers for this are, above all, short development times and high-quality requirements, leading to tight tolerances. To overcome the resulting challenges, many publications address the process-oriented tolerance management. However, since multiple terms and definitions for describing activities that link tolerance management with the production process exist, it is hard to obtain a comprehensive overview on the topic. Therefore, this paper presents a review of existing approaches. The aim is to identify similarities and differences of existing approaches and present them with the help of a classification. For this purpose, among others, work from the areas of process-oriented tolerance management, stream of variation, state space modeling, and variation propagation in multistation manufacturing and assembly systems is considered. Based on the definition of the summarizing term “process-oriented tolerance and variation management”, a classification of this thematic area will be introduced.<br
Keywords: process-oriented tolerancing; stream of variation; state space modeling; process-oriented tolerance and variation management